2016
DOI: 10.5604/17331331.1204473
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Glycosylation of Flavonoids

Abstract: A b s t r a c tFlavonoids constitute a large group of polyphenolic compounds naturally found in plants, which have a wide range of biological activity. Although flavonoids are beneficial to human health, their application is limited by their low bioavailability and poor water-solubility. Therefore, recently there has been a particular interest in glycosylated forms of flavonoids, which usually are better soluble, more stable, and more functional compared to their aglycones. Microbial transformation of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Furthermore, flavonoids, as effective antioxidant molecules, display a strong protective effect against cold temperatures and UV radiation in plants [ 18 , 39 , 40 ]. Research has shown that glycosylation improve the bioactivities of flavonoids, such as an increase in water solubility and the diversification in biological function [ 41 , 42 ], and this is beneficial for plants in terms of tolerating abiotic and biotic stresses [ 43 ]. In addition, Huang et al [ 44 ] found that the antioxidant activity exerted by catechins is proportionate to the degree of gallate derivatization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, flavonoids, as effective antioxidant molecules, display a strong protective effect against cold temperatures and UV radiation in plants [ 18 , 39 , 40 ]. Research has shown that glycosylation improve the bioactivities of flavonoids, such as an increase in water solubility and the diversification in biological function [ 41 , 42 ], and this is beneficial for plants in terms of tolerating abiotic and biotic stresses [ 43 ]. In addition, Huang et al [ 44 ] found that the antioxidant activity exerted by catechins is proportionate to the degree of gallate derivatization.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding human beneficial effects, flavonoids are usually restrained by their low bioavailability due to undesirable water solubility, and this defect can be overcome by glycosylation [ 41 , 45 ], thus broadening applications for human health. For instance, hesperetin 7- O -glucoside has been reported to be superior to hesperetin and hesperidin for inhibiting human intestinal maltase [ 46 ], and the bioactivity of catechins is largely determined by the degree of gallate derivatization [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction is catalyzed by the superfamily of enzymes called UDP-glycosyltransferases (UGTs) with over 90 families, which catalyze the transfer of UDP-activated sugar moieties to specific acceptor molecules [ 8 , 9 ]. The glycosyltransferases are involved in production of biomass, maintain cellular homeostasis by regulating the active levels of hormones, stabilize anthocyanin structures, influence transport of biomolecules by modifying their solubility, and modify bioavailability of plant secondary metabolites [ 15 ]. There are two types of glycosyltransferases: Leloir-type and non-Leloir-type.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions catalyzed by glycosyltransferases are regio- and stereoselective. They may proceed either with retention or inversion of the configuration at the anomeric carbon atom of the substrate [ 15 ]. The least numerous group of glycosyltransferases that are capable of glycosylation of flavonoids comprises microorganisms’ enzymes, such as BcGT-1 from Bacillus cereus , DSM-13 and YjiC from Bacillus licheniformis , OleD from Streptomyces antibioticus and XcGT-2 from Xanthomonas campestris [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biotransformations of flavonoids is a useful tool to obtain their glycosylated derivatives. Application of microorganisms as biocatalysts allows us to obtain these compounds in sufficient amounts for research, e.g., the effect of a glycoside group on compound properties and for further application as ingredients of dietary supplements and pharmaceuticals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%